EFL Freshmen’s Writing Performances: A Rural and Urban School Perspective - Syafitri Ramadhani; Ainul Addinna; Carbiriena Solusia; Dian Safitri; Abu Bakar Razali; Zhyldyz Takenova (English Department FBS UNP, 2025)
The inputs comprehended by freshmen when they were at high schools contribute much to their present writing performance. However, the influence of school location towards this issue is still debatable and gets minor attention to explore in its relationship towards the recent courses. This study is comparative which aims to compare and see the differences in several writing aspects, including content, organization, and language features among freshmen who graduated from rural senior high schools and urban senior high schools. A writing test was administered to collect the students’ writing documents which were analysed by employing content analysis to reveal the differences, supported by an Independent T-test and Mann Whitney U test to find their significance. This study uncovered that rural freshmen generally performed better than urban freshmen did. Conversely, it voices the support on equality and inclusivity of rural and urban freshmen on academic environment, thus leading the existence of no diversity between both groups. Implicitly, this study advices further researchers to investigate any existing gap or discrimination among students regarding their school origins, and to effectively unravel the issues, achieving SDG 4 and EFA.